2007
DOI: 10.1007/s10750-006-0474-8
|View full text |Cite
|
Sign up to set email alerts
|

Diatom assemblages in sediments of Lake Juusa, Southern Estonia with an assessment of their habitat

Abstract: Diatom analysis of surface sediments and two sediment cores from different sedimentation areas of a small closed lake was undertaken with the aim of acquiring knowledge on the dependence of the distribution of diatom assemblages on lake bathymetry. Lake Juusa was selected for the study because we have for this lake a large data set about the lithological composition of sediments and macrofossil and cladoceran records for the Holocene. A high carbonate content (20-60%) in the sediment sequence indicates high ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 47 publications
1
11
0
1
Order By: Relevance
“…In addition, the appearance of Cyclotella ocellata in the fossil record of lakes has commonly been interpreted as indicating higher lake water levels (e.g. Punning and Puusepp 2007 (Conedera et al 2004). In addition, the development of the effect of climate cannot be ruled out, the evidence points to major human impact that changed the forest structure after 4650 cal.…”
Section: Climatic Versus Anthropogenic Forcing In the Picos De Europamentioning
confidence: 99%
“…In addition, the appearance of Cyclotella ocellata in the fossil record of lakes has commonly been interpreted as indicating higher lake water levels (e.g. Punning and Puusepp 2007 (Conedera et al 2004). In addition, the development of the effect of climate cannot be ruled out, the evidence points to major human impact that changed the forest structure after 4650 cal.…”
Section: Climatic Versus Anthropogenic Forcing In the Picos De Europamentioning
confidence: 99%
“…Lake-level fluctuations have been reconstructed successfully using changes in diatom assemblages in other regions (Punning and Puusepp 2007;Laird and Cumming 2008). Diatom-inferred changes in depth have been employed most successfully in lakes where the ratio of planktonic to benthic species was the dominant change during a deepening or shallowing of the lake (Brugam et al 1998;Laird and Cumming 2008).…”
Section: Lake-level Reconstructionsmentioning
confidence: 99%
“…Laird and Cumming (2008), for example, compared diatom-inferred depths with instrumental records from an Ontario lake; they found that lake level decreases of 0.2-0.3 m during the drought of the 1980s were not reflected by the diatom-based record of depth, but larger changes of several meters to tens of meters over the Holocene matched well with changes in depth inferred from other proxies. Some studies have shown that more robust models for diatom variability with depth can be developed by using a calibration set based on shallow-to-deep water transects within an individual lake rather than by using a suite of lakes with a range of maximum depths as has been done here (Punning and Puusepp 2007;Laird and Cumming 2008).…”
Section: Resolution and Datingmentioning
confidence: 99%
“…Among the periphyton community the most likely assemblage to be affected by low lake levels are the epiphytic forms attached to plants. In addition, in freshwater lakes, fluctuations of the water level could be a steering factor determining the habitats of diatom assemblages in the lake (Punning & Puusepp, 2007). WLF also affect phytoplankton development (abundance, biomass, size structure, taxonomic composition, species diversity and rate of community compositional change) (de Emiliani, 1997;Noges & Laugaste, 1998;Coops & Hosper, 2002;de Domitrovic, 2003;Kangur et al, 2003;Stockner et al, 2005).…”
Section: Effects On Biotamentioning
confidence: 99%